Adjustable Buckle-Slide Suture: A Novel Surgical Technique for Transscleral Fixation of Intraocular Lenses. (October 2019) - Zhao, Peiquan; Ou, Zhongmin; Zhang, Qi; Jin, Haiying
Abstract : Supplemental Digital Content is Available in the Text.